Homoarginine and ornithine production during C2C12 myogenic differentiation - Zhloba, Alexandr; Subbotina, Tatiana; Prikhodko, Stanislava; Khudiakov, Alexandr; Smolina, Natalia; Kostareva, Anna (Biological Communications, 2018)
Assessment of cellular rates of amino acid consumption and release in vitro allows the study of cell culture in a time-course experiment without any cell damage. Determination of the release of amino acid metabolites that initially were not present in the media provides more reliable information about the processes of growth and differentiation in comparison with determination of amino acid consumption rates. Homoarginine (hArg), a derivative of arginine, is generated as the minor product in the reaction catalyzed by L-Arginine: glycine amidinotransferase, where L-lysine serves as an acceptor for amidine group instead of glycine. Ornithine is another product generated in this reaction from arginine. Thus, the goal of the present study was to evaluate the rate of hArg and ornithine accumulation in comparison to the rate of consumption of other amino acids in the course of C2C12 myoblast differentiation. The release time profiles were similar for hArg and ornithine, with the maximum corresponding to the second day of differentiation. The shift for hArg at this time point was detected with greater reliability (p < 0.002) than for ornithine and other amino acids. We suggest that hArg and ornithine could serve as markers to monitor the processes of myoblasts growth and differentiation.